Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMP Negeri 1 Sampolawa - Iriana, Artati; Armin, Rismayani; Alsum, Alsum (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
Objective of this research is to find out the influence of learning motivation toward students learning proficiency of mathematics at grade VIII of SMP Negeri 1 Sampolawa. This research was an ex post facto research. Population in this research was all grade VIII students of SMP Negeri 1 Sampolawa whose number was 140 students. Sample of this research was 57 students whom was selected through simple random sampling technique. Instrument of the research were questionnaire and documentation. Based on the research outcome, it is concluded that there is a positive and significant influence of learning motivation toward students learning proficiency of mathematics at grade VIII of SMP Negeri 1 Sampolawa. This can be seen by the result of analysis that value of was 19,781 > was 4,02. Besides, the determination coefficient was 0,265 or 25,50% of mathematics proficiency was explained by variable of learning motivation, while the rest was influenced by other factors that were not observed in this research